DIFUSI INOVASI PAKLAY KOMPLIT (PAKET LAYANAN KOMPLIT) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KARANGANYAR - Siti Adiyani Ayu Prasetyowati; Kismartini Kismartini; Retna Hanani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The PAKLAY Komplit (Paket Layanan Komplit) innovation is a superior innovation created by the Karanganyar Regency Population and Civil Registration Service with the aim of overcoming population administration service problems in Karanganyar Regency. However, the implementation of the Complete PAKLAY innovation still experiences problems, namely rejection of application documents, lack of information regarding requirements, website errors, and not being able to log in to your PAKLAY account. The objectives of this research are (1) to analyze the diffusion process of PAKLAY Komplit innovation, (2) to identify the driving and inhibiting factors of the diffusion process of PAKLAY Komplit innovation. The method used in this research is qualitative with descriptive research type. Data collection techniques use observation, interviews and documentation. The phenomenon of this research is observed based on the important elements of innovation diffusion, namely innovation, communication channels, time period and social system and the factors that encourage and inhibit the process of innovation diffusion. The research results show that, overall, the PAKLAY Komplit innovation meets the characteristics of innovation. The communication channels used are interpersonal channels and mass media channels. Karanganyar Disdukcapil employees and the community have different times in accepting and using the Complete PAKLAY innovation. Types of adopters are identified in four groups, namely innovators, early adopters, early majority, and late majority. The supporting factors for implementing the diffusion of PAKLAY Komplit innovation are organizational culture, individuals, and knowledge of innovation and reinvention. Meanwhile, the inhibiting factors are psychological obstacles and practical obstacles. Recommendations that can be given are giving rewards to employees so that they are more innovative and the importance of improving the quality of public information such as banners, posters and billboards in each sub-district/village